Inspired Cross-Stitch : 30 Patterns Plus Alphabets - Bussi, Gail; Zucker, Gale (Lanham, Maryland (MD) : STACKPOLE BOOKS, 2021)
Stitch your way to a better day! The 30 cross-stitch designs in Gail Bussi's signature chalk art, hand-lettering style, will encourage mindful, relaxing stitching and are easy enough for beginners. The patterns are divided into sections to Inspire, Create, or Connect, and will give you positive thoughts for many occasions. Finished pieces are perfect for sharing your hopes and wishes for others, or to keep to remind yourself of your personal aspirations. As you stitch the meaningful sayings, let the words as well as the simple movements inspire you. Ready to stitch your own favorite mantra? Use alphabets provided to design your own pieces. Finish your pieces as small pillows, hangings, framed wall art, book covers, or however you envision. Each project includes chart, finished photo, materials list, and full instructions.
Includes visual index
Keywords: Cross-stitch; Cross-stitch -- Patterns; Pattern books; Patterns (Instructional works)